Edukasi Gizi Tentang Kebiasaan Konsumsi Kopi dengan Kejadian Hipertensi pada Remaja - Tri Ardianti Khasanah; Meyra Sakura Kinanti Mukti; Fawnia Dwiayu Wijayanti; Ni’ma Ghida Alfaz; Suti Patimah; Nisrina Dhia Lathifah; Hesty Hulandari; Raisha Sonia; Maulana Farid Rizky; Mufidah Lia Santoso (Lembaga Pengembangan Kinerja Dosen, 2025)
Coffee is a drink that the Indonesian people have long favored. Coffee can affect blood pressure because polyphenols and potassium lower blood pressure, while caffeine increases blood pressure. The World Health Organization (WHO) has estimated that by 2025, 1.5 billion people in the world will suffer from hypertension per year. Blood pressure in adolescents who experience hypertension can have a higher risk of morbidity and mortality, not only that the more severe hypertension experienced in adolescents can lead to a fairly severe risk of complications such as heart attack, stroke, and coronary artery disease. This study aims to provide broad insights related to nutrition and hopes that our education can at least change the mindset of adolescents regarding the importance of frequent coffee consumption without clear reasons. This study used the Wilcoxon Signed Ranks Test method.This nutrition education was conducted at SMK Harapan Massa, Beji, Depok. On January 25, 2024. Using Descriptive Research type. Based on Wilcoxon analysis, 45 students experienced a decrease in scores, 3 students experienced an increase and 16 students had similar scores in the post-test and pre-test. Conclusion. there is an influence on the results of students' understanding before exposure to the material (Post-test) and after exposure (Pre-test).